Cytokine Storm in COVID-19 Patients, Its Impact on Organs and Potential Treatment by QTY Code-Designed Detergent-Free Chemokine Receptors - Mujahed I. Mustafa; Abdelrahman H. Abdelmoneim; Eiman M. Mahmoud; Abdelrafie M. Makhawi (Hindawi Limited, 2020)
The novel coronavirus is not only causing respiratory problems, but it may also damage the heart, kidneys, liver, and other organs; in Wuhan, 14 to 30% of COVID-19 patients have lost their kidney function and now require either dialysis or kidney transplants. The novel coronavirus gains entry into humans by targeting the ACE2 receptor that found on lung cells, which destroy human lungs through cytokine storms, and this leads to hyperinflammation, forcing the immune cells to destroy healthy cells. This is why some COVID-19 patients need intensive care. The inflammatory chemicals released during COVID-19 infection cause the liver to produce proteins that defend the body from infections. However, these proteins can cause blood clotting, which can clog blood vessels in the heart and other organs; as a result, the organs are deprived of oxygen and nutrients which could ultimately lead to multiorgan failure and consequent progression to acute lung injury, acute respiratory distress syndrome, and often death. However, there are novel protein modification tools called the QTY code, which are similar in their structure to antibodies, which could provide a solution to excess cytokines. These synthetic proteins can be injected into the body to bind the excess cytokines created by the cytokine storm; this will eventually remove the excessive cytokines and inhibit the severe symptoms caused by the COVID-19 infection. In this review, we will focus on cytokine storm in COVID-19 patients, their impact on the body organs, and the potential treatment by QTY code-designed detergent-free chemokine receptors.